Prevalence of Infections Caused by Hepatitis B Virus, Hepatitis C Virus and Their Co-Infection in A Tertiary Care Centre, Delhi, India - Manoj Kumar; Sanjay Jain (Journal of Epidemiology and Public Health, 2025)
Background: Hepatitis B and C are the most dominant causes of viral hepatitis, leading to both acute and chronic infections. This study was done to determine the magnitude of the prevalence of Hepatitis B and C and their co-infection.Subjects and Method: A retrospective cross-sectional observational study was conducted in the Department of Microbiology, North DMC Medical College and Hindu Rao Hospital, Delhi, India from July 2023 to June 2024. All blood samples received from indoor and outdoor patients from all departments were tested by Monolisa HBsAg Ultra and anti-HCV(Ag-Ab Ultra V2) Monolisa by ELISA method. The variables studied were age, sex, in-patient/out-patient, and type of ward. The data was analyzed using the Chi-Square test and Mann-Whitney test.Results: Of a total of 20,000 blood samples received, 5,358(26.80%) samples were from inpatient department/IPD (2,210 female, 3,148 male) and 14642 (73.20%) and outpatient department/OPD (9,201 female, 5,441 male). 422 samples (2.11%) were positive for HBsAg (210 IPD -77 female, 133 male; 212 OPD - 121 female, 91 male) and 614 (3.07%) for anti-HCV (408 IPD - 135 female, 273 male; 206 OPD - 100 female, 106 male). Co-infection of Hepatitis B and C viruses was seen in 40 patients, 31 IPD (10 female, 21 male) and 9 OPD (1 female, 8 male). Maximum cases were seen from medicine wards among IPD patients of HBsAg positive, anti-HCV positive, and co-infection and in the age group 41-60 years in all three categories.Conclusion: Screening for HBV and HCV infection is compulsory so that preventive measures are implemented to improve public health.